Giant Dermatofibrosarcoma Protuberans Of The Frontoparietal Area: A Case Report - Adam Rizky; Hatibie Mendy; Yuansun Kosama; Tjandra Djony (Green Publisher Indonesia, 2024)
Background: Dermatofibrosarcoma protuberans (DFSP) is a rare, slow-growing, low to intermediate-grade soft tissue sarcoma. It is commonly found on the trunk, representing approximately 1-2% of all soft tissue sarcomas. Still, it may also manifest in the extremities or the head and neck, typically in adult patients. It is a locally aggressive neoplasm that tends to infiltrate adjacent structures but with a low potential for metastatic potential. It often presents complex clinical problems due to its high rates of recurrence. Purpose: The study aims to analyze the clinical and histopathological characteristics of DFSP through case reports, as well as provide guidance for effective treatment strategies. Method: We report a case of a 40-year-old male with a complaint of a recurring giant mass of the frontal area. Before the current complaint, the patient had undergone three separate surgeries for a mass growing in the exact location. The pathologic diagnosis was dermatofibrosarcoma protuberans. Result: The patient had undergone three previous surgeries for the same mass, with a histopathological diagnosis of DFSP. After a complete surgical excision with a wider margin, the patient showed no signs of recurrence four months after surgery. Conclusion: Considering the extent of the current mass, excision was chosen as the primary treatment, with wider surgical margins due to the infiltrative growth nature of the neoplasm. The patient was then followed up four months post-operation, showing no signs of recidivism.